2019
DOI: 10.1111/epi.16356
|View full text |Cite
|
Sign up to set email alerts
|

Realistic driving simulation during generalized epileptiform discharges to identify electroencephalographic features related to motor vehicle safety: Feasibility and pilot study

Abstract: Objective: Generalized epileptiform discharges (GEDs) can occur during seizures or without obvious clinical accompaniment. Motor vehicle driving risk during apparently subclinical GEDs is uncertain. Our goals were to develop a feasible, realistic test to evaluate driving safety during GEDs, and to begin evaluating electroencephalographic (EEG) features in relation to driving safety. Methods: Subjects were aged ≥15 years with generalized epilepsy, GEDs on EEG, and no clinical seizures. Using a high-fidelity dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 29 publications
4
35
0
Order By: Relevance
“…IEDs have prolonged reaction times in a driving simulation task (Krestel et al, 2011;Nirkko et al, 2016), and increased crash rate when virtual obstacle is presented (Nirkko et al, 2016) IEDs prolonged reaction time in a variable manner, with generalized discharges affecting RT greater than focal discharges (Nirkko et al, 2016); and longer and higher voltage IEDs exerting a greater effect (Cohen et al, 2020).…”
Section: Hippocampal Ieds Decrease Memory Performance and Prolong Reamentioning
confidence: 99%
“…IEDs have prolonged reaction times in a driving simulation task (Krestel et al, 2011;Nirkko et al, 2016), and increased crash rate when virtual obstacle is presented (Nirkko et al, 2016) IEDs prolonged reaction time in a variable manner, with generalized discharges affecting RT greater than focal discharges (Nirkko et al, 2016); and longer and higher voltage IEDs exerting a greater effect (Cohen et al, 2020).…”
Section: Hippocampal Ieds Decrease Memory Performance and Prolong Reamentioning
confidence: 99%
“…The simulator we used reflected typical driving conditions, where severely impaired driving behaviors or collisions would be detected, but more subtle deficits might be missed. Methods with sudden unexpected obstacles coinciding with epileptiform activity can detect delayed reaction times or other subtle deficits in driving, which we may have missed here 8,15,17 . This may be particularly true for GSWs (including slow spike–wave), where we rarely found deficits with the current approach, whereas more instantaneous testing methods are capable of uncovering deficits 8,11,15,17 .…”
Section: Discussionmentioning
confidence: 86%
“…Many studies have shown that with better clinical testing, transitory cognitive impairment, manifest most commonly as increased reaction time, accompanies these seemingly subclinical discharges. [1][2][3][4] In early experiments from the 1940s, the discharge bursts lasting 1-3 seconds had normal reaction times, and longer bursts showed impairment. 1 Nevertheless, some other studies showed an increase in reaction time even with short bursts lasting 0.5-1.5 seconds; however, there was no increase in errors of omission during such short bursts.…”
Section: Discussionmentioning
confidence: 99%
“…This pilot study showed that generalized spike-wave discharges with no response to stimuli were significantly longer than those with appropriate responses (8.47 ± 3.10 vs 1.85 ± 0.69 seconds, p < 0.001). 4 Again, the study had a low sample size of 9 although 88 bursts were studied. Although the data regarding this are limited, as discussed above, there is a suggestion of correlation of transitory cognitive impairment with duration of generalized spike-wave bursts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation